2013
DOI: 10.1142/s0192415x13500250
|View full text |Cite
|
Sign up to set email alerts
|

Preventive and Therapeutic Effects of Ginsenoside Rb1 for Neural Injury During Cerebral Infarction in Rats

Abstract: To examine the preventive and therapeutic effects of ginsenoside Rb1 for neural injury during cerebral infarction, we used a middle cerebral artery occlusion (MCAO) model in rats to investigate the effects of ginsenoside Rb1 with Edaravone as a control. Ginsenoside Rb1 was given to the rats by intragastric administration either before or after the MCAO surgery to study its preventive and therapeutic effects. Ginsenoside Rb1-treated rats had a smaller infarct volume than the positive control. Interleukin-1 (IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…However, both the anti-apoptotic and antiproliferative capacities of ginsenoside Rb1 on different cell types under diverse pathological conditions were reported previously. For instance, ginsenoside Rb1 reduced ischemia/reperfusion-induced apoptosis of cardiomyocytes and neurocytes [39,40], while the anticancer property of ginsenoside Rb1 was exhibited through its inhibition of melanoma cell proliferation [41]. Li et al [42] demonstrated that ginsenoside Rb1 inhibited FBS-induced proliferation of rat aortic smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, both the anti-apoptotic and antiproliferative capacities of ginsenoside Rb1 on different cell types under diverse pathological conditions were reported previously. For instance, ginsenoside Rb1 reduced ischemia/reperfusion-induced apoptosis of cardiomyocytes and neurocytes [39,40], while the anticancer property of ginsenoside Rb1 was exhibited through its inhibition of melanoma cell proliferation [41]. Li et al [42] demonstrated that ginsenoside Rb1 inhibited FBS-induced proliferation of rat aortic smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…Through reading the full text of the remaining 541 articles, 513 studies were further removed with at least one of reasons as follows: (1) not in vivo studies; (2) not focal cerebral ischemia; (3) not G-Rb1 intervention or combined with other treatment. Eventually, we included 28 studies (Zhang et al, 1998;Tao, 2004;Li et al, 2005;Ren, 2005;Fan, 2006;Zhang et al, 2006;Yoshikawa et al, 2008;Gao et al, 2010;Lu, 2010;Lu et al, 2011;Lv, 2011;Zhu et al, 2012;Jiang et al, 2013;Liu et al, 2013;Yu et al, 2013;Liu et al, 2014;Zeng et al, 2014;Chen et al, 2015;Dai et al, 2016;He et al, 2016;Lv et al, 2016;Dong et al, 2017;Gao, 2017;Li et al, 2018;Liu et al, 2018;Xu et al, 2018;Sun and Xiu, 2018;Shi et al, 2019) in the final analysis. The process of screening is summarized in a flow diagram ( Figure 2).…”
Section: Study Selectionmentioning
confidence: 99%
“…Twelve studies were published in English and the remainder in Chinese. The animal species included Sprague-Dawley (SD) rats (Tao, 2004;Li et al, 2005;Ren, 2005;Fan, 2006;Lu, 2010;Lu et al, 2011;Zhu et al, 2012;Jiang et al, 2013;Liu et al, 2013;Yu et al, 2013;Liu et al, 2014;Dai et al, 2016;He et al, 2016;Li et al, 2018;Sun and Xiu, 2018;Xu et al, 2018;Shi et al, 2019), Wistar rats (Gao et al, 2010;Liu et al, 2018), stroke-prone spontaneously hypertensive rats (SHR-SP) (Zhang et al, 1998;Zhang et al, 2006), C57BL/6 mice (Zeng et al, 2014;Lv et al, 2016;Dong et al, 2017;Gao, 2017), BALB/c mice (Lv, 2011), Institute of Cancer Research (ICR) mice (Chen et al, 2015) and Cynomolgus monkeys (Yoshikawa et al, 2008). Chloral hydrate was used in 18 studies (Tao, 2004;Li et al, 2005;Ren, 2005;Fan, 2006;Lu, 2010;Lu et al, 2011;Lv, 2011;Jiang et al, 2013;Liu et al, 2013;Yu et al, 2013;Liu et al, 2014;Dai et al, 2016;He et al, 2016;…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Previous studies have found that ginsenoside Rb1/Rg1 can alleviate impairments in learning and memory, and regulate the cholinergic system in a variety of experimental animal models. In addition, ginsenoside Rb1/Rg1 exerts a protective effect on dopamine neurons by reducing the stress response induced by 1-methyl-4-phenyl 2,3,6-tetrahydropyridine/1-methyl-4-phenyl pyridine, and also alleviates tau hyperphosphorylation through regulation of the activities of glycogen synthase kinase 3β and protein phosphatase 2A[404142434445464748]. The present study demonstrates the protective effect of ginsenoside Rb1 on the damage to cerebral cortical neurons in rats mediated by hypoxia-activated microglia.…”
Section: Discussionmentioning
confidence: 99%